Ethics of Interpretation of Symbolic Texts - Polishchuk, Yaroslav (Poznańskie Studia Slawistyczne, 2022)
The main subject of the review is Mykola Ilnytskyi’s book Reading and Re-reading…, which is very important research on Ukrainian literature in contemporary humanities. The book includes four chapters in all of which fundamental interests of the researcher are described. Mykola Ilnytskyi reviews the classic texts of Taras Shevchenko, Ivan Franko ( chapter 1 ), and the literature of the first part of the 20th century ( chapter 2 ), as well as contemporary texts ( chapters 3, 4 ). This book is not an extensive view of the history of literature of the 20th century. Its main peculiarity is the delivery of important fragments and episodes of literary history. The essays combine a liberal understanding of the subject and an unobtrusive interpretation of the texts, which reflects the unique ethical culture of the researcher. Mykola Ilnytskyi is clearly aware of the multiplicity of meanings offered byfiction, and therefore does not insist on his own right to the truth, but only offers well-founded and personally verified versions of literary plots.